PROKRASTINASI AKADEMIK DITINJAU DARI REGULASI DIRI DAN ADVERSITY QUOTIENT PADA MAHASISWA YANG BEKERJA DI PERGURUAN TINGGI “X” YOGYAKARTA - Asti Kusuma Wardani; Mayrena Nurwardani (UIN Sunan Kalijaga, 2019)
Abstract. Students are the person that devepelopment to preparing themselves for accept the responsibility as fully adult person. In college period, students are free with their study time system. The part time worker usually has a problem with their time management. That can be affect with their academic in college. Their usually didn’t have so much time to doing their task in college. The procrastination can happen by the part time worker because of so many activity. This reseacrh used quantitative method and data are collected by using likert scale to 100 students who part time worker in “X” University. The analytical data showed that the significantcy number is 0,000 (p<0,005). Data showed the mayor hypothesis are approved that means sifnificant correlation between self regulation and adversity quotient with academic procrastination. Self regulation and adversity quotient affect 30,4% and 69,6% affect with other variable.Keyword: time worker, students, academic procrastination, self regulation, adversity quotient